Managerial Economics : a Game Theoretic Approach. - Fisher, Tim (Taylor and Francis, 2014)
This book can be used as a way of introducing business and management students to economic concepts as well as providing economics students with a clear grasp of how to use the skills they will need in the world of business. Topics covered include:*product differentiation*price discrimination*hiring and training workers*labor-management relations*international tradeA host of key features are employed to add colour to the text including case studies, examples and discussion questions. Scenarios presented centre upon a diverse range of subjects and firms including Eurostar, NHL hockey equipment.